Mapping of quantitative trait loci for seedling salt tolerance in maize - Luo, Meijie; Zhang, Yunxia; Chen, Kuan; Kong, Mengsi; Song, Wei; Lu, Baishan; Shi, Yaxing; Zhao, Yanxin; Zhao, Jiuran (Molecular breeding, 2019)
Improved salt tolerance is a major goal for maize breeders, but the control of salt tolerance-related traits in maize is poorly understood. A set of 209 doubled haploid (DH) lines derived from the maize hybrid Xianyu335 was genotyped using 1335 single-nucleotide polymorphism (SNP) markers. Biomass-related traits under salt stress were used as salt tolerance indicators, and a quantitative trait loci (QTL) analysis was conducted in hydroponic culture under salt-stress and normal conditions. Fourteen traits showed significant phenotypic differences between parents, and 16 traits showed transgressive segregation in the DH population. We detected 65 QTL: 41 associated with salt tolerance and 24 related to normal growth. Salt tolerance-related QTL clustered on chromosomes 1, 3, 7, and 9, among which 13 major effect QTL on chromosome 1 individually explained more than 21% of the phenotypic variation. Of these large-effect QTL, QTL controlling seven traits upon salt treatment and two salt tolerance indexes were co-located; they extensively overlapped with the remaining four co-localized QTL related to four other salt tolerance indexes. The QTL identified here shed new light on the molecular mechanism of salt tolerance in maize and may provide robust functional markers for marker-assisted selection of salt tolerant maize varieties.